Stylistic Analysis of Figurative Language in Nadzira Shafa’s 172 Days: A Qualitative Study of Indonesian Contemporary Novel - Sony Julian Saputra (JPI: Jurnal Pustaka Indonesia, 2024)
Language style is one of the essential elements in literature, as it not only enhances the aesthetic quality of a text but also conveys the author’s intentions, emotions, and cultural context. This study aimed to analyze the use of language styles in Nadzira Shafa’s novel 172 Days to identify the forms and functions of stylistic devices within a contemporary Indonesian popular literary work. The research employed a qualitative descriptive approach, with data collected through repeated and comprehensive readings of the text, followed by classification and interpretation of stylistic features, including comparison, contradiction, linkage, and repetition. The results reveal a wide range of rhetorical devices, such as simile, metaphor, personification, symbolism, allegory, hyperbole, paradox, parallelism, and tautology, each contributing to the narrative’s emotional depth, thematic reinforcement, and cultural resonance. The discussion indicates that these stylistic elements not only shape character development and narrative flow but also highlight the richness of Indonesian literary expression in modern popular novels. The implication of this study is that stylistic analysis provides both theoretical insights into the development of Indonesian literature and practical applications in literary pedagogy, offering a bridge between classical stylistics and contemporary texts that are more relatable to younger readers.